Perbandingan Metode Pembelajaran Role Playing Dengan Metode Konvensional (Ceramah) Terhadap Hasil Belajar Siswa - Dori Oktavian; Sulaiman Sulaiman (Prodi Pendidikan Keagamaan Islam, 2022)
The background is the low learning outcomes of Islamic Religious Education, especially in the cognitive domain at school due to the lack of activeness of students in class and shyness to ask if the material is not understood. Based on observations at SMK Negeri 1 Lintau Buo, the learning process is more teacher-centered (TCL). Therefore, new variations or modern learning methods are needed to generate activity and train students' self-confidence, as well as a place for discussion between students, as a result the Role Playing method is established to improve student learning outcomes. The purpose of Role-Playing research is to find out the comparison of learning outcomes using the Role Playing learning method with the Conventional method (Lecture) on the learning outcomes of class XI students of SMK Negeri 1 Lintau Buo. This type of research is pre-experimental, and the research design is randomized control group posttest only. The population in this study were all class XI SMK Negeri 1 Lintau Buo, while the samples were class XI TITL Experiment class and XI TKJ control class. The sampling technique was purposive sampling. The results of data analysis showed that the average value of the experimental class was higher than the control class using the Role Playing learning method providing a significant difference, as evidenced by the hypothesis test using SPSS version 25, the data obtained was 0.00 < 0.05, where the value of Sig ( 2-tailed) < or 0.05 so that Ho is rejected and Ha is accepted. the conclusion is that there are differences in learning outcomes using the Role Playing method with conventional methods on the learning outcomes of class XI students at SMK Negeri 1 Lintau Buo.